THE EFFECT OF WORKING CAPITAL ON LIQUIDITY IN SAVINGS AND LOANS COOPERATIVES IN TAPUNG HILIR DISTRICT, KAMPAR REGENCY - Nur Aisyah; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to test: (1) to find out and analyze the working capital in the savings and loan cooperatives in Tapung Hilir District, Kampar Regency, (2) to find out and analyze liquidity in the savings savings cooperatives in Tapung Hilir Sub-District, Kampar Regency, ( 3) to analyze the effect of working capital on liquidity in savings cooperatives in the Tapung Hilir District of Kampar Regency. Where the independent variable in this research is Working Capital and the dependent variable is Liquidity. This research uses secondary data in the form of Annual Cooperative Members Meeting Report for 2009-2018. Data analysis in this study used simple linear regression, t test, and the coefficient of determination using the SPSS 16 program. The results of the analysis show that the Working Capital variable (t-test) partially influences the Liquidity of the Saving and Loan Cooperative in Tapung Hilir District, Kampar Regency. Keywords: Working Capital and Liquidity      Keywords: Working Capital and Liquidity